Perceptions of family support and college support: the mediating roles of hope and peer support. Issue 2 (7th February 2022) - George-Levi, Sivan; Laslo-Roth, Roni; Bareket Bojmel, Liad; Margalit, Malka
ABSTRACT: Perceptions of social support contribute to positive adjustment even more than the actual provision of support. The goals of this study were to identify factors that may promote positive perceptions of the provision of on-campus support, especially in stressful times. The present study aimed to examine the predictive role of interpersonal resources (family and peer support) and intrapersonal resources (hope) in explaining perceptions of college support among students during the outbreak of the COVID-19 pandemic. Five hundred and eighty-seven college students (474 females and 113 males) participated in the study (mean age = 26.27, SD = 4.83). A serial mediation model demonstrated that hope and support from peers mediated the relations between perceived family support and perceived on-campus support. The important role of perceived family support during the young adults' age stage in promoting additional types of support and personal resources is discussed. Practical implications for developing supportive college environments, including direct interventions to activate hope and enhance the development of various types of support, are considered.